The Story of Repairs Against the Background of the Boundless Lie: the Palace of Wedding in Irkutsk - Zhizhchenko, Elena (project baikal, 2018)
The article tells about the competition for the design for repair of the Palace of Wedding in Irkutsk and its realization. It touches upon the participation of the author and the architect in designing the repairs and the necessity of the designer's supervision. It criticizes inappropriate actions of the planning institution that realized the design for repair.
Keywords: Palace of Wedding in Irkutsk; OOO Sibniisromproekt; Town-Planning Committee; Irkutsk Department for Architecture and Town-Planning; Irkutsk Town- Planning Council; the Office of Vital Records; Irkutsk Regional Organization of the Union of Architects of